Edukasi Risiko Mialgia pada Komunitas Lansia Kalirejo, Malang - Adam Samudra Humaidy; Abdul Rahmat Amin Mayu; Achmad Banu Mustofa; Raymond Oskar; Dinda Camela Damayanti; Faiqatul Qari’ah; Nadya Setyarini Farizka; Bayu Prastowo (Lembaga Pengembangan Kinerja Dosen, 2025)
Myalgia is a muscle pain condition that can occur in a specific area of the body or spread to several regions. Its main symptoms include pain, soreness, or discomfort in the muscles, whether during movement or at rest. The pain may range from mild to severe and is sometimes accompanied by stiffness, muscle tension, or even cramps that interfere with daily activities. This condition is commonly experienced by the elderly due to aging, loss of muscle mass, improper physical activity, stress, lack of stretching, or an unhealthy lifestyle. This community service activity aimed to provide education and raise awareness about myalgia among 10 elderly participants in the Elderly Community of Kalirejo, Malang, to help them better understand prevention, pain management, and self-care strategies. The method used was service learning (SL) with achievement parameters measured through pre-test and post-test evaluations. The results showed an increase in participants’ knowledge regarding the definition, causes, and rehabilitation of myalgia from 10% to 90%, demonstrating that this program effectively improved the elderly’s understanding and awareness of myalgia.